2014
DOI: 10.1089/brain.2014.0247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deafferentation from Spinal Anesthesia on Pain Sensitivity and Resting-State Functional Brain Connectivity in Healthy Male Volunteers

Abstract: Patients may perceive paradoxical heat sensation during spinal anesthesia. This could be due to deafferentation-related functional changes at cortical, subcortical, or spinal levels. In the current study, the effect of spinal deafferentation on sensory (pain) sensitivity was studied and linked to whole-brain functional connectivity as assessed by resting-state functional magnetic resonance imaging (RS-fMRI) imaging. Deafferentation was induced by sham or spinal anesthesia (15 mg bupivacaine injected at L3-4) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…6567 Studies using acute pain models have found decreased thalamic FC to multiple pain-related brain regions that were associated with reductions in clinical pain. 66, 67 Additional studies in chronic pain conditions such as fibromyalgia have implicated thalamic FC changes as a potential underlying feature of chronic pain. 6870 Ichesco et al 68 noted increased THAL-DMN FC was associated with increased pain in patients with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…6567 Studies using acute pain models have found decreased thalamic FC to multiple pain-related brain regions that were associated with reductions in clinical pain. 66, 67 Additional studies in chronic pain conditions such as fibromyalgia have implicated thalamic FC changes as a potential underlying feature of chronic pain. 6870 Ichesco et al 68 noted increased THAL-DMN FC was associated with increased pain in patients with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Cole et al have illustrated that three non‐overlapping seeds, all taken from the posterior part of the default mode network (DMN), produce extensive non‐overlapping cortical connectivity maps [Cole et al, ]. On the plus side, these anatomical variations in network topography help explore the regional specificity of the response of specific brain regions, for example sub‐nuclei of the thalamus [Niesters et al, ], or subsections of the hippocampus [Khalili‐Mahani et al, ], to drugs that are expected to target these regions.…”
Section: Basics and Biomarkersmentioning
confidence: 99%
“…Using the putamen as a seed, Upadhyay et al showed a dose‐dependent decreases in functional connectivity of the somatosensory and sensorimotor networks [Upadhyay et al, ] under buprenorphine, with a topography that closely resembled an NOI‐based analysis of the morphine effect on these networks in an independent study [Khalili‐Mahani et al, ] prominent effects in the hippocampus and sensorimotor networks. A dose‐dependent increase in functional connectivity of the frontoparietal and thalamocortical regions has been shown to correlate with pain perception in spinal anesthesia using bupivacaine [Niesters et al, ]. A dose‐dependent ketamine‐induced increase in the functional connectivity of the corticohippocampal subnetworks has also been reported concurrent with reduced alertness states [Khalili‐Mahani et al, ].…”
Section: Experimental Objectives and Clinical Relevancementioning
confidence: 99%
See 2 more Smart Citations